Faricimab for retinal vein occlusion: a review of current evidence and future perspectives - Jing, Yongjie; Li, Daming (Frontiers in Pharmacology, 2025)
Retinal vein occlusion (RVO) is the second most common retinal vascular cause of vision loss after diabetic retinopathy and can lead to substantial visual impairment due to retinal ischemia, hemorrhage, vascular leakage, and macular edema. Intravitreal anti-vascular endothelial growth factor (VEGF) therapy is currently the first-line treatment for RVO-associated macular edema, with its efficacy confirmed by numerous large-scale randomized controlled trials. However, VEGF is not the only pathological driver in RVO. Angiopoietin-2 (Ang-2) has emerged as a key factor that contributes to disease progression by destabilizing the vascular endothelium through disruption of the Tie2 signaling pathway, increasing vascular permeability, and intensifying inflammation. Faricimab is a bispecific monoclonal antibody that targets both VEGF-A and Ang-2, providing a dual mechanism of action that includes anti-permeability, anti-angiogenic, and anti-inflammatory effects. In both the BALATON and COMINO trials, patients with RVO achieved mean best-corrected visual acuity (BCVA) improvements of approximately +17 to +19 letters, along with central subfield thickness (CST) reductions exceeding 300 μm in both treatment arms after Faricimab treatment. Compared to traditional single-target anti-VEGF agents, Faricimab has demonstrated non-inferior or even superior outcomes in visual and anatomical improvements, while also offering extended dosing intervals and reduced treatment burden. Nevertheless, its safety profile positions it mid-range among anti-VEGF therapies. This review outlines the molecular rationale, key clinical trial data, comparative efficacy and safety, and current challenges and future directions for Faricimab in RVO management, aiming to inform its clinical application in RVO and broader retinal vascular disorders.